The Effect Of Acceptent And Commitment Therapy On Increasing Nurse Student's Commitment In The Online Learning Process During The Covid-19 Pandemic - Ira Ayu Maryuti (Jambura Nursing Journal, 2023)
During the Covid-19 pandemic, the face-to-face learning system has changed to online. Online learning poses several problems for students. Online learning is difficult to reach, making students lazy and bored. During online learning, students' commitment and motivation in learning cannot be explained. This study aims to analyze the effect of Acceptance and Commitment Therapy (ACT) on the commitment of nursing students in the courageous learning process during the covid-19 pandemic. This study uses a pre-experimental research design with Pretest-Posttest Design. The target population is 2nd semester students who carry out online learning at the Faculty of Nursing, Citra Bangsa University, Kupang, as many as 62 students, who were pre-tested with a commitment score below 126. Sampling was carried out by the total sampling method, which was 20 students. 5 students did not become respondents to become respondents, 3 respondents did not attend since the 2nd session due to illness, a total of 12 respondents. The independent variable was Acceptance and Commitment Therapy (ACT) and the variable was commitment. The research instrument is a commitment questionnaire. Data analysis used a paired test with 0.05, first the normality test will be carried out. The results of the study were based on hypothesis testing which was carried out on the commitment obtained p = 0.000 (